1978
DOI: 10.1007/bf00381635
|View full text |Cite
|
Sign up to set email alerts
|

Some clinically relevant variables affecting the mechanical behaviour of bone cement

Abstract: The effects of 12 clinically relevant variables upon the basic mechanical properties of acrylic cement are reported. Attention is drawn to the facts that these variables may at times coexist to lead to serious reductions in the strength of the cement, and that the operating surgeon may exercise a substantial influence on the effective mechanical properties of the cement he is using.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
14

Year Published

1980
1980
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 14 publications
0
34
0
14
Order By: Relevance
“…Holm (1977) reported that the flexural modulus of elasticity of CMW cement was reduced by up to 21% by the addition of 3 mL of blood, but that the same amount of blood reduced the strength of Palacos by only 3%. Lee et al (1978) mixed 1 mL of blood in the cement mass (Simplex P) and showed a reduction in ultimate compressive strength between 8% and 16%. The experiment revealed rather high standard deviations, indicating unpredictable behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holm (1977) reported that the flexural modulus of elasticity of CMW cement was reduced by up to 21% by the addition of 3 mL of blood, but that the same amount of blood reduced the strength of Palacos by only 3%. Lee et al (1978) mixed 1 mL of blood in the cement mass (Simplex P) and showed a reduction in ultimate compressive strength between 8% and 16%. The experiment revealed rather high standard deviations, indicating unpredictable behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that bleeding from the bone bed during cementation reduces the strength of the cement-bone interface (Benjamin et al 1987, Bannister and Miles 1988, Majkowski et al 1994. It has also been demonstrated that, under certain circumstances, inclusion of blood in the cement mass or in laminations appearing during cementation reduces the mechanical strength of the bone cement (Gruen et al 1976, Holm 1977, Lee et al 1978, Saha and Pal 1984.…”
Section: Gunnar Flivik Xunhua Yuan Leif Ryd Rigmor Juliusson and Lmentioning
confidence: 99%
“…This phenomenon Malkani et al 1996, Kärrholm et al 1999, Ullmark and Nilsson 1999, Lee 2000b Gie et al 1993, Nilsson and Kärrholm 1996, Eldridge et al 1997b, Kuiper et al 1998, Brewster et al 1999, Mikhail et al 1999; c Lee et al 1978, Alfaro-Adrian et al 1999, Stefánsdóttir et al 1999d Dohmae et al 1988, Taylor andTanner 1997 (Eldridge et al 1997a, Ullmark 2000, size distribution (Brewster et al 1999), delipidization (Kärrholm et al 1999, Ullmark 2000, and size and stiffness of the graft (Kuiper et al 1998). In most studies neither the chip size (Gie et al 1993, Weidenhielm et al 1994, Eldridge et al 1997b, Meding et al 1997, Kärrholm et al 1999, Mikhail et al 1999, Knight et al 2000 nor the type of morselizer used has been reported (Gie et al 1993, Weidenhielm et al 1994, Eldridge et al 1997b, Meding et al 1997, Kärrholm et al 1999, Mikhail et al 1999.…”
Section: Compression and Slippage Of The Allograft Bonementioning
confidence: 99%
“…in the first three months) (Lee et al 1978, Lee 2000, Hughes et al 1997. The design of the Exeter stem is consistent with migration within the cement leading to wedging and new settling in the cement mantle (Ling 1986, Fowler et al 1988.…”
Section: Cold Flow and Creep Of The Cementmentioning
confidence: 99%
“…lt should be remarked that bone cement is somewhat viscoelastic, hence d ifferences instrain rate may, apart from other circumstances, explain the variety in resu lts to some ex tent. Lee et al (1978) Lee et al,7978).…”
Section: Conditionsmentioning
confidence: 99%